Tinjauan identiti dan bahasa hibrid dalam kalangan Samsam, Baba Nyonya dan Jawi Peranakan di Utara Semenanjung Malaysia - Noriah Mohamed; Omar Yusoff (Universiti Kebangsaan Malaysia, 2010)
This paper reviews and discusses the identity and language of three groups that were considered to display the hybrid (half-breed) feature. The group is Samsam, Baba Nyonya and Jawi Peranakan that reside in the northern part of West Malaysia. The data for this study was gathered from the library research and non-structured interview which was conducted through field studies on the informants from the three groups. The description of the data was done in a descriptive qualitative manner. In general, this survey identified that the hybrid is a concept that exhibit the characteristics of a system formed from a combination of different subsystems or parts. This hybrid concept was used to describe the identity of the three groups. From the language point of view although the language spoken by all the three groups show features of hybrid, however the classification in terms of linguistic show that the speech system of Samsam and Jawi Peranakan were considered as dialect, while the Baba Nyonya speech system was Creole status. This article also discusses the aspects of linguistic classification of the speech of the three groups as intended. This paper is useful because owing to it we can trail the history of the three oldest hybrid groups that exist in Malaysia